Project Schedule Performance of IFI Financed Public Projects: Evidence from Uzbekistan - Yakubova Samira; Makhmudov Mirkhojidin (Goodwood Publishing, 2026)
Purpose: This study aims to assess the schedule performance of public-sector investment projects financed by major international financial institutions (IFIs) in Uzbekistan, focusing on the differences in implementation timelines based on funding institutions, project size, and sectoral characteristics. Research methodology: Using publicly available data on IFI-financed projects approved between 2010 and 2024, this study evaluates project performance through planned versus actual implementation duration, time overruns, and formal project extensions. Descriptive statistics, non-parametric tests, and logistic regression models were employed to analyze the probability of schedule extensions while controlling for project size, sector, and approval year. Results: The analysis revealed significant variations in schedule performance across IFIs, with larger infrastructure projects having a higher likelihood of delays. Conclusions: The findings suggest that institutional governance and project monitoring play crucial roles in the management of project time. Limitations: The study relies on publicly available data, which may not capture all project variables, and is limited to projects financed by specific IFIs. Contributions: This research contributes to the understanding of project schedule performance in transition economies and highlights the value of using open, transparent data for comparative performance studies, providing policy insights for improving schedule risk management in similar contexts.